Influence of Technology-Enhanced Physics Instruction on Academic Performance of High School Students in Anambra State, Nigeria - Izunna Shedrack Nwuba; Abdurahman Hakimi; Abdoul Kadri Diallo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
The persistent decline in students' academic performance in physics has become a major concern in secondary education systems across developing countries, including Nigeria. Conventional teaching methods, characterized by teacher-centered instruction and limited instructional resources, have been identified as key contributors to this challenge. This study examined the influence of technology-enhanced physics instruction on the academic performance of high school students in Anambra State, Nigeria. A quasi-experimental pretest–posttest control group design was adopted. A total of 180 senior secondary school II students were selected using a multistage sampling technique and assigned to experimental and control groups. The experimental group was taught selected physics concepts using technology-enhanced instructional strategies, including computer simulations, multimedia presentations, and virtual experiments, while the control group received conventional lecture-based instruction. Data were collected using a validated Physics Achievement Test (PAT), and analysis was conducted using descriptive statistics and Analysis of Covariance (ANCOVA). The results revealed a statistically significant difference in academic performance between students exposed to technology-enhanced instruction and those taught using traditional methods (p < 0.05). Students in the experimental group demonstrated superior achievement scores, indicating that technology-enhanced physics instruction significantly improved learning outcomes. The findings highlight the pedagogical value of integrating digital technologies into physics classrooms to enhance student engagement and academic achievement. The study concludes that technology-enhanced instruction is an effective approach for improving physics education in Nigerian secondary schools and recommends sustained investment in digital infrastructure and teacher professional development.